2013
DOI: 10.1128/jvi.02024-12
|View full text |Cite
|
Sign up to set email alerts
|

The Compensatory G88R Change Is Essential in Restoring the Normal Functions of Influenza A/WSN/33 Virus Matrix Protein 1 with a Disrupted Nuclear Localization Signal

Abstract: b G88R emerged as a compensatory mutation in matrix protein 1 (M1) of influenza virus A/WSN/33 when its nuclear localization signal (NLS) was disrupted by R101S and R105S substitutions. The resultant M1 triple mutant M(NLS-88R) regained replication efficiency in vitro while remaining attenuated in vivo with the potential of being a live vaccine candidate. To understand why G88R was favored by the virus as a compensatory change for the NLS loss and resultant replication deficiency, three more M1 triple mutants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“… [12] . Xie et al, using computational protein–protein docking techniques along with the 1EA2 structure, have also proposed a model in which adjacent M1 N 1–165 domains may be stacked against one another so as to maximize the electrostatic interaction of the NLS region and nearby basic residues with a cluster of negatively-charged residues of the opposite M1 face and also the M1–M1 steric interactions [10] . This model may be more representative of M1 in its biological environment because it relies only on electrostatic and shape complementarity rather than crystal packing forces to obtain tetrameric structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… [12] . Xie et al, using computational protein–protein docking techniques along with the 1EA2 structure, have also proposed a model in which adjacent M1 N 1–165 domains may be stacked against one another so as to maximize the electrostatic interaction of the NLS region and nearby basic residues with a cluster of negatively-charged residues of the opposite M1 face and also the M1–M1 steric interactions [10] . This model may be more representative of M1 in its biological environment because it relies only on electrostatic and shape complementarity rather than crystal packing forces to obtain tetrameric structures.…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal domain (1–165 aa) of M1 was subcloned into pET30b (Novagen) from a pHW2000 plasmid expressing the full-length A/WSN/33 M1 [10] at the cloning sites of Nde1+Xho1. The new plasmid pET30b-M1wt-1–165 with a His-tag at the N-terminus (5′-primer: actagccatatgcaccatcatcatcatcatagtcttctaaccgaggtc; 3′-primer: tctgatctcgagctacatttgcctatgagaccgatg) was expressed in E. coli strain Nico21(DE3) (NEB).…”
Section: Methodsmentioning
confidence: 99%
“… 30 As a result, M(NLS-88R) not only has a thick M1 layer in assembled virions but also replicates efficiently in vitro and in vivo , similar to the parent virus WSN. 30 , 31 In contrast, M(NLS-88E) has a thin M1 layer in mature virions and replicates inefficiently in vitro and in vivo . 30 Using M(NLS-88R) and M(NLS-88E) as model viruses, we revealed that the transition from a face-to-back orientation at neutral pH to a face-to-face orientation at acidic pH allows M1 to quickly dissociate from vRNP for efficient replication.…”
Section: Introductionmentioning
confidence: 95%
“…Both M(NLS-88R) and M(NLS-88E) are M1 mutants in the WSN background that differ in a single mutation at M1 position 88 (G88R vs G88E). 30 G88R but not G88E was originally acquired by the virus as a spontaneous compensatory mutation after NLS disruption. 30 As a result, M(NLS-88R) not only has a thick M1 layer in assembled virions but also replicates efficiently in vitro and in vivo , similar to the parent virus WSN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation